Clinical Outcomes and patient Satisfaction after Vaginal versus Abdominal Hysterectomy for benign Gynecological Conditions - Saniya Naheed, Saleha Hassan, Azra Kanwal, Muneeba Sadaf, Shazia Afzal, Nuzhat Nazar Cheema (Pakistan Journal of Medical & Health Sciences, 2024)
Background: One of the most common operations done to the gynecological system is hysterectomy, which is performed when the disorder is benign. The decision-making of the surgical path is critical in deciding the outcomes of the perioperative period, the postoperative healing, and patient satisfaction. Hysterectomy of the vagina and abdomen is a common practice that is mainly used in cases involving tertiary care but there is a lack of comparative local data assessing their clinical outcomes and patient satisfaction. Materials and Methods: The retrospective study was comparative and done in the department of Obstetrics & Gynaecology, Watim Medical & Dental College, Islamabad. Reviewed medical records of 120 women aged 30-65 years old with benign gynecological conditions that had hysterectomy between January 2023 and June 2023. The surgical approach was used to categorize the patients into two groups (vaginal hysterectomy, n = 58, and abdominal hysterectomy, n = 62). The collected data were demographic details, operative indication, operative time, estimated blood loss, post operative complications, hospital stay, and patient satisfaction recorded in the follow- up records. The data were analyzed by means of SPSS version 25, and the independent t-tests and the chi-square tests were used to make the comparisons. Results: The vaginal hysterectomy had been related to a substantially reduced time of operation, less intraoperative bleeding, lesser duration of stay, and less occurrence of complications after surgery in comparison to the abdominal hysterectomy ( p 0.05). The vaginal hysterectomy group showed much higher levels of patient satisfaction, earlier return of ability to resume normal daily activities and cosmetic results. Conclusion: Vaginal hysterectomy has better clinical disaster and greater patient satisfaction than abdominal hysterectomy in the case of benign gynecological problems and must be viewed as the method of choice surgery in the right patients. Keywords: Vaginal hysterectomy; Abdominal hysterectomy; Patient satisfaction; Clinical outcomes.